Spectral compression and entanglement reduction in the cascaded biphoton state with cavities. (11th November 2021) - Wong, Y-E; Tsai, N-Y; Hiew, W S; Jen, H H
Abstract: The cascaded biphoton state generated from a cold atomic ensemble presents one of the strongly correlated resources that can preserve and relay quantum information. Under the four-wave mixing condition, the emitted signal and idler photons from the upper and lower excited states become highly correlated in their traveling directions and entangled in continuous frequency spaces. In this system, we theoretically study the spectral compression of the biphoton source using an external cavity and show the reduction in its frequency entanglement entropy. This indicates, respectively, an improved light absorption efficiency for the idler photon as well as an almost pure biphoton source which is useful in optical quantum networks. We further investigate the limit of the spectral compression that can be achieved by using multiple cavities. Our results show the capability and potential of the biphoton source with external cavities, where the performance of atom-based quantum memory can be enhanced and the entanglement property can be manipulated by tailoring the spectral compression.